Immunological Outcome in Haploidentical-HSC Transplanted Patients Treated with IL-10-Anergized Donor T Cells - Bacchetta, Rosa; Lucarelli, Barbarella; Sartirana, Claudia; Gregori, Silvia; Lupo Stanghellini, Maria Teresa; Miqueu, Patrick; Tomiuk, Stefan; Hernandez-Fuentes, Maria; Gianolini, Monica Emma; Greco, Raffaella; Bernardi, Massimo; Zappone, Elisabetta; et al. (Frontiers in Immunology, 2014)
T-cell therapy after hematopoietic stem cell transplantation (HSCT) has been used alone or in combination with immunosuppression to cure hematologic malignancies and to prevent recurrence. Here, we describe the outcome of patients with high-risk/advanced stage hematologic malignancies, who received T-cell depleted (TCD) haploidentical-HSC transplantation (haplo-HSCT) combined with donor T lymphocytes pretreated with IL-10 (ALT-TEN trial). IL-10 anergized donor T cells (IL-10 DLI) contained T regulatory type 1 (Tr1) cell specific for the, host alloantigens, limiting donor-vs-host reactivity, and memory T cells able to respond to pathogens. IL-10 DLI were infused in 12 patients with the goal of improving immune-reconstitution after haplo-HSCT without increasing the risk of GvHD. IL-10 DLI led to fast immune-reconstitution in five patients. In four out of the five patients, total T-cell counts, TCR-Vβ repertoire and T-cell functions progressively normalized after IL-10 DLI. These four patients are alive, in complete disease remission and immune suppression-free at 7.2 years (median follow-up) after haplo-HSCT. Transient GvHD was observed in the immune reconstituted patients, despite persistent host-specific hypo-responsiveness of donor T cells in vitro and enrichment of cells with Tr1- specific biomarkers in vivo. Gene expression profiles of immune-reconstituted patients showed a common signature of tolerance. This study provides the first indication of the feasibility of Tr1 cell-based therapy and paves the way for the use of these Tr1 cells as adjuvant treatment for malignancies and immune-mediated disorders.